Canaliculotomy as A Canalicular Obstruction Management Approach: a Case Series (Majalah Kedokteran Bandung, 2022)
Lacrimal drainage obstruction is a common disorder of lacrimal system. This obstruction could affect lacrimal punctum, canaliculi, lacrimal sac, and lacrimal duct. The etiology could be congenital or acquired, such as triggered by infection or other  conditions. This case series illustrates the procedure of canaliculotomy to reduce the epiphora symptom caused by lacrimal drainage obstruction, specifically in punctum and canaliculi. The aim of this case series was to report the management of punctal and canaliculi obstruction with canaliculotomy procedure. Case 1, an eighty-two years old woman with chronic canaliculitis on the right eye due to Actynomyces sp. infection, underwent canaliculotomy and curetage of canalicular area of the right eye. Case 2, a sixty-years old man with chronic canaliculitis with canalicular fistula on the left eye underwent canaliculotomy with silicone tube procedure on the left eye. Case 3, a sixty-seven years old man with recurrent punctal obstruction due to punctal stenosis of the left eye, previous punctoplasty, underwent canaliculotomy with silicone tube. Identification of the patient's symptoms is very important in determining the diagnosis and management plan for the patient. Canaliculotomy procedure with antimicrobial and steroid medication after procedure leads to a good result in reducing symptoms caused by lacrimal drainage obstruction due to various etiology.
Keywords: Canalicular obstruction; Canaliculotomy; Punctoplasty